Types of coproduction and differential effects on organizational performance: evidence from the New York City school system - Zambrano-Gutierrez, Julio Cesar; Nicholson-Crotty, Sean; Rutherford, Amanda (2017)
A growing body of literature explores the process of coproduction by citizens and government employees in providing goods and services, yet research that attempts to link coproduction to organizational performance offers contradictory findings. It is possible that these conflicting results are a consequence of trying to compare distinct categories of coproduction. This study identifies types of coproduction, classified by which organizational tasks citizens can influence during stages of policy design and implementation, and tests whether these types have different effects on student proficiency in Mathematics and English Language Arts using data from New York City schools between 2007 and 2009. This study then tests the degree to which different types of coproduction moderate the negative effect of environmental turbulence on performance. Results confirm that types of coproduction have varying effects on organizational performance and can reduce, and even eliminate, the negative effect of a turbulent environment on student outcomes. - Reproduced.
Keywords: Schools; Organizations